Kualitas Hidup Lansia dengan Demensia dan Peran Dukungan Keluarga serta Lingkungan Perawatan di Poli Jiwa: Quality of Life of Elderly with Dementia and the Role of Family Support and the Care Environment in Mental Health Clinics - Nurpah; Rima Berlian Putri; Roza Indra Yeni; Ricky Riyanto Iksan (Journal of Nursing Education and Practice, 2026)
Introduction: Dementia is a major health problem in older adults that affects cognitive function, psychosocial well-being, and overall quality of life. Cognitive decline in elderly individuals with dementia can lead to increased dependence and decreased daily functioning, which ultimately impacts their quality of life if not properly managed.Objectives: This study aims to describe the quality of life of elderly people with dementia in the mental health clinic at Hospital X.Method: This study used a descriptive quantitative design. The population included all elderly patients with dementia who visited the Mental Health Clinic at Hospital X. A total sampling technique was applied, involving 43 respondents. Data were collected using a questionnaire measuring quality of life and analyzed using univariate analysis to describe the distribution of variables.Results: The findings showed that the majority of elderly people with dementia had a good quality of life, while the rest were categorized as having a poor quality of life. The mean score indicated relatively small variation among respondents, suggesting that most participants had comparable quality of life conditions.Conclusion: Most elderly people with dementia in the Mental Health Clinic at Hospital X have a good quality of life. These findings provide a basis for developing appropriate nursing interventions and health services to improve the well-being of elderly patients with dementia.